Hubungan Kemampuan Membaca Kritis dengan Kemampuan Menulis Argumentasi Siswa Kelas XI SMAN 1 Kinali - Utami, Yesi Setya; Ratna, Ellya; Chan, Wirsal (Universitas Negeri Padang, 2012)
This study aimed to describe the following three things. First, it describes the critical reading skills class XI student of SMA Negeri 1 Kinali. Second, describe the writing skills of students of class XI argument SMA Negeri 1 Kinali. Third, analyze the relationship between students' critical reading skills with the ability to write a class XI student argumentation SMA Negeri 1 Kinali. Data collection was conducted through two tests, the objective tests and performance tests. Analyzing the data is done in accordance with the application of the concept of descriptive research korelasi.Berdasarkan data analysis concluded three things. First, critical reading skills class XI student of SMAN 1 Kinali are in good qualifying (80.28). Second, the ability to write arguments class XI student SMAN 1 Kinali are in good qualifying (79.72). Third, there is a significant relationship between critical reading skills with the ability to write a class XI student argumentation SMA Negeri 1 Kinali.